Identification of strategic activities in the process of adoption of the methodology by cases applied to the students of the accounting course for the improvement of their academic performance, Arequipa, 2019 - Ramírez-Lazo, P.C. (2019)
This work was focused on identifying the strategic cycle for the application of the methodology by cases in administration students; for this an evaluation was carried out with the methodology to capture perceptions and gathering of relevant information where criteria were identified to propose a new route of strategic case-based learning in order to improve assertive performance, expertise and debatability in students. The research identified that only 2% are dissatisfied with the application of the methodology and more than 81% would like it to be implemented in their final evaluations. However, 76% believe that there should be improvements, in the same way in that the gathering of information identified is important to carry out a simulation of the experience and consider preparation and evaluation as a risk factor for its adoption in relation to the performance of the teaching moderator. The strategic cycle identified has a high preference for students, this could be implemented after improving some points.